Efficacy of enfortumab vedotin in advanced urothelial cancer: Analysis from the Urothelial Cancer Network to Investigate Therapeutic Experiences (UNITE) study. Issue 6 (9th December 2021) - Koshkin, Vadim S.; Henderson, Nicholas; James, Marihella; Natesan, Divya; Freeman, Dory; Nizam, Amanda; Su, Christopher T.; Khaki, Ali Raza; Osterman, Chelsea K.; Glover, Michael J.; Chiang, Ryan; Makrakis, Dimitrios; et al.
Abstract : Background: Enfortumab vedotin (EV) is a novel antibody‐drug conjugate approved for advanced urothelial cancer (aUC) refractory to prior therapy. In the Urothelial Cancer Network to Investigate Therapeutic Experiences (UNITE) study, the authors looked at the experience with EV in patient subsets of interest for which activity had not been well defined in clinical trials. Methods: UNITE was a retrospective study of patients with aUC treated with recently approved agents. This initial analysis focused on patients treated with EV. Patient data were abstracted from chart reviews by investigators at each site. The observed response rate (ORR) was investigator‐assessed for patients with at least 1 post‐baseline scan or clear evidence of clinical progression. ORRs were compared across subsets of interest for patients treated with EV monotherapy. Results: The initial UNITE analysis included 304 patients from 16 institutions; 260 of these patients were treated with EV monotherapy and included in the analyses. In the monotherapy cohort, the ORR was 52%, and it was >40% in all reported subsets of interest, including patients with comorbidities previously excluded from clinical trials (baseline renal impairment, diabetes, and neuropathy) and patients with fibroblast growth factor receptor 3 ( FGFR3 ) alterations. Progression‐free survival and overall survival were 6.8 and 14.4 months, respectively. Patients with a pure urothelial histology had a higher ORR than patients with a variant histology component (58% vs 42%; P = .06). Conclusions: In a large retrospective cohort, responses to EV monotherapy were consistent with data previously reported in clinical trials and were also observed in various patient subsets, including patients with variant histology, patients with FGFR3 alterations, and patients previously excluded from clinical trials with an estimated glomerular filtration rate < 30 mL/min and significant comorbidities. Lay Summary: Enfortumab vedotin, approved by the Food and Drug Administration in 2019, is an important new drug for the treatment of patients with advanced bladder cancer. This study looks at the effectiveness of enfortumab vedotin as it has been used at multiple centers since approval, and focuses on important patient populations previously excluded from clinical trials. These populations include patients with decreased kidney function, diabetes, and important mutations. Enfortumab vedotin is effective for treating these patients. Previously reported clinical trial data have been replicated in this real‐world setting, and support the use of this drug in broader patient populations. Abstract : On the basis of initial data from the Urothelial Cancer Network to Investigate Therapeutic Experiences study, enfortumab vedotin has activity in diverse populations of patients with urothelial cancer, including patients with variant histologies, patients with FGFR3 alterations, and patients with significant comorbidities previously excluded from clinical trials. Additionally, in this large, multi‐institutional, retrospective cohort of patients with urothelial cancer, responses to enfortumab vedotin in patients treated outside a clinical trial are consistent with and complementary to prior clinical trial data.